2008
DOI: 10.17221/31/2008-pps
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and spreading of Macrophomina phaseolina(Tassi) Goidanovich on sunflower in the Czech Republic

Abstract: VEVERKA K., PALICOVÁ J., KŘÍŽKOVÁ I. (2008): . Plant Protect. Sci., 44: 127–137. The warm climate pathogen <i>Macrophomina phaseolina</i> (Tassi) Goid., which causes charcoal disease, has been reported in the Czech Republic since 1999. The aim of our work was to study the incidence of disease between 2000–2007 in the main sunflower growing regions and analyse the relationship between weather conditions and the occurrence of the pathogen. The first and highest incidence of disease was in the Žatec r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…It is widespread throughout Latin America, Eastern and Southern Africa, Egypt, West Asia, Middle East including Iran and Turkey (Habib et al 2007, Mahmoud and Budak 2011, Ijaj et al 2012, and South Asia, more particularly in Pakistan (Khan 2007). With change in climate, the diseases are also reported to occur in the otherwise relatively cooler regions of the United States (Gulya et al 2002, Ullah et al 2011, Weems et al 2011 and Europe (Sarova et al 2003, Bokor 2007, Veverka et al 2008, Csondes et al 2012. Crop loss estimates are available to the extent of 64% in the Krasnodar region of Russia, 46% in India , and 90% in Pakistan (Khan 2007).…”
Section: Geographical Distribution and Lossesmentioning
confidence: 99%
“…It is widespread throughout Latin America, Eastern and Southern Africa, Egypt, West Asia, Middle East including Iran and Turkey (Habib et al 2007, Mahmoud and Budak 2011, Ijaj et al 2012, and South Asia, more particularly in Pakistan (Khan 2007). With change in climate, the diseases are also reported to occur in the otherwise relatively cooler regions of the United States (Gulya et al 2002, Ullah et al 2011, Weems et al 2011 and Europe (Sarova et al 2003, Bokor 2007, Veverka et al 2008, Csondes et al 2012. Crop loss estimates are available to the extent of 64% in the Krasnodar region of Russia, 46% in India , and 90% in Pakistan (Khan 2007).…”
Section: Geographical Distribution and Lossesmentioning
confidence: 99%
“…The isolated fungi were identified according to their morphological characteristics, represented by M. phaseolina according to Veverka [12]. While R. solani, was identified based on the characteristics of the fungal culture and the microscopic characteristics mentioned in Parmeter and Whitney [13], then the isolates were kept in test tubes containing sterile PDA supplied with antibiotic.…”
Section: Morphologic Characterization Of Fungimentioning
confidence: 99%
“…It is commonly registered in Pakistan (JALIL et al, 2013), China (ZHANG et al, 2016), and India (SURIACHANDRASELVAN et al, 2005), where reported yield losses were up to 90% in sunflower. In favourable years, the fungus was registered in the European countries as well, including Spain (JIMENÉZ-DIAZ et al, 1983), Italy (MANICI et al, 1992), Hungary (CSÖNDES et al, 2011), Slovakia (BOKOR, 2007, the Czech Republic (VEVERKA et al, 2008), Romania (IONITĂ et al, 1996, Bulgaria (ALEXANDROV, 1999) and Serbia (TANČIĆ et al, 2012). Generally, charcoal rot caused by this pathogen can reduce seed yields by 20-36% throughout the world (JIMENEZ-DIAZ et al, 1983) caused by premature ripening.…”
Section: Introductionmentioning
confidence: 99%